2006
DOI: 10.1097/00001786-200607000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Testing of the National Database of Nursing Quality Indicators Pressure Ulcer Indicator

Abstract: A criterion-referenced Web-based test was designed and administered to 256 individuals at 48 randomly sampled National Database of Nursing Quality Indicators (NDNQI) member hospitals to determine the reliability of the NDNQI pressure ulcer indicator. Overall kappa values for pressure ulcer identification, staging, and sourcing indicate moderate to near perfect reliability. Findings suggest that nurses can accurately differentiate pressure ulcers from other ulcerous wounds in Web-based photographs, reliably sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…When these assumptions are violated, Cohen's j cannot be used to indicate the consistency of the ratings between two raters. For instance, Hart et al (2006) reported Cohen's j between hospital nurses and PU experts. Ratings made by experts were considered correct classifications and the reliability between nurses and experts was considered rater-to-standards reliability.…”
Section: Resultsmentioning
confidence: 99%
“…When these assumptions are violated, Cohen's j cannot be used to indicate the consistency of the ratings between two raters. For instance, Hart et al (2006) reported Cohen's j between hospital nurses and PU experts. Ratings made by experts were considered correct classifications and the reliability between nurses and experts was considered rater-to-standards reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Hart et al,16 in a Web-based examination designed to test the reliability of the pressure ulcer measure of the National Database of Nursing Quality Indicators (NDNQI) and to assess 256 nurses’ knowledge of pressure ulcers, found that registered nurses certified in wound, continence, and/or ostomy care scored significantly higher than did other nurses in staging of ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Here we included data from all observation periods, irrespective of the estimate . Sun performed subgroup analyses of studies according to the degree of training of the raters involved, and also drew a distinction between inter-rater reliability studies where both raters can be considered to be equivalent and a study [14] comparing ratings from hospital nurses with those from an expert which would more appropriately have been analysed using sensitivity, specificity and related techniques. The QuIS observations were carried out by raters who had all received the training developed by McLean et al: though there was variation in experience of QuIS a further source of inter-rater unreliability relating to the different lines of view from each rater’s position was also considered to be important.…”
Section: Discussionmentioning
confidence: 99%